Beneficial effects of the whole-body cryotherapy on sport haemolysis - Banfi, G.; Melegati, G.; Barassi, A.; d'Edril, G. M. (Journal of Human Sport & Exercise, 2009)
Background. Sport's anemia is a common risk for athletes. The principal source of an accelerated turnover of the erythrocytes in sportsmen is the intravascular hemolysis. This phenomenon is induced by mechanical breakage for impact of feet and muscular contractions, but also by osmotic changes causing membrane fragility, typically evident after exercise, when free radicals are increased. Whole-body cryotherapy (WBC) covers a wide range of therapeutic applications and consists of briefly exposing the body to extremely cold air. In sports medicine, WBC is used to improve recovery from muscle injury; however, empirical studies on its application to this area are lacking. Design and Methods. We recruited ten rugby players of the Italian National Team. In these athletes we measured hematological parameters, before including mean sphered cell volume (MSCV) by means of Coulter LH750, besides of haptoglobin, and after WBC. The subjects underwent five sessions on alternate days once daily for one week. During the study period, the training workload was the same as that of the previous weeks. Results. We observed in the athletes increase of haptoglobin and an increase of MSCV after the treament period. Conclusions. WBC reduces sports haemolysis, as judged from MSCV and haptoglobin data, supported from other haematological values, as well as the absence of mean corpuscolar volume and reticulocytes increase. The treatment is useful to prevent the physiological impairments derived from sport haemolysis